2016
DOI: 10.1016/j.bbmt.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety Outcomes in Patients with Hematological Malignancies Undergoing Autologous Hematopoietic Stem Cell Transplantation Treated with Palifermin to Prevent Oral Mucositis

Abstract: The purpose of our study was to compare long-term safety outcomes (overall survival, disease progression, and incidence of secondary malignancies) between palifermin and placebo in the prevention of oral mucositis in patients with hematological malignancies undergoing autologous hematopoietic stem cell transplantation (HSCT). Patients were enrolled between 1997 and 2005 into 4 phase I to III studies (3 double-blind placebo-controlled and 1 open-label) conducted at 31 sites in Australia, Europe, and the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
4
1
1
Order By: Relevance
“…Theoretically, there is a risk that palifermin may stimulate secondary malignancies, because the KGF receptor is expressed on epithelial cells of many tissues, and it is thus of high importance to study this theoretical risk at exposure in children and adolescents. Long-term follow-up of subjects receiving palifermin in adult hematologic malignancy studies treated with myeloablative therapy and allogeneic HSCT has not shown an increased incidence of secondary malignancies or decrease in PFS or OS over historical data [32]. The PFS and OS in this study did not differ from what would be expected historically in pediatric patients with hematologic malignancies treated in a similar way as patients in this study [33].…”
Section: Discussioncontrasting
confidence: 41%
“…Theoretically, there is a risk that palifermin may stimulate secondary malignancies, because the KGF receptor is expressed on epithelial cells of many tissues, and it is thus of high importance to study this theoretical risk at exposure in children and adolescents. Long-term follow-up of subjects receiving palifermin in adult hematologic malignancy studies treated with myeloablative therapy and allogeneic HSCT has not shown an increased incidence of secondary malignancies or decrease in PFS or OS over historical data [32]. The PFS and OS in this study did not differ from what would be expected historically in pediatric patients with hematologic malignancies treated in a similar way as patients in this study [33].…”
Section: Discussioncontrasting
confidence: 41%
“…9 Similarly, in a randomized, double-blind trial of adults undergoing allogenic HCT; palifermin treatment had no significant effect on time to engraftment, aGVHD, or survival. 8 …”
Section: Discussionmentioning
confidence: 96%
“…1 However, cells of the hematopoietic lineage do not express the KGF receptor, and the administration of palifermin for the prevention of OM in patients with hematologic malignancies does not appear to adversely affect other HCT outcomes. 9 However, most of these outcomes, including outcomes pertinent to safety (e.g. mortality and count recovery) were largely evaluated in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, survival of patients receiving palifermin and the placebo were almost the same [61]. Moreover, according to Stiff et al, the long term safety outcomes among patients receiving palifermin in oral mucositis treatment and the placebo were comparable [63].…”
Section: Management Of Oral Mucositismentioning
confidence: 94%